Adjusting to the energy shock: The right policies for European industry - Giovanni Sgaravatti; Simone Tagliapietra; Georg Zachmann (Bruegel, 2023)
In 2022, overall European Union industrial employment and output increased above 2021 levels, despite rocketing energy prices. However, output declined from energy-intensive industries including basic metals, chemicals, non-metallic minerals and paper, for which energy costs represent a much bigger share of production costs than for less energy-intensive manufacturing. Energy prices are likely to remain above historic levels for the foreseeable future. In its industrial strategy response to this context, the EU must ask first whether the energy-intensive parts of the value chain should be outsourced permanently. Conditional on the answer being no, the second question is how to reduce energy prices to ensure the competitiveness of the energy-intensive productions stages that remain in the EU. First, the EU could bridge the high energy price period with unconditional subsidies, which seems to be the preferred strategy currently. This will avoid irreversible large-scale relocation abroad but is expensive, does not help to drive down energy prices and poses risks of fragmentation within the EU. It will only succeed if internationally competitive energy supplies are made available quickly. Second, the EU could support decarbonised production processes built on large-scale deployment of domestic renewables, grid interconnectors and storage. This would accelerate the green transition and reduce clean-tech prices worldwide. However, EU taxpayers would bear the cost of new technologies, without any guarantee of solving the current cost-competitiveness issue. Third, the EU could facilitate imports of energy-intensive products, while helping EU industry move to higher value-added parts of the value chain. Subsidies could be given directly to industrial sectors that have not become structurally uncompetitive, while bringing down energy demand and thus energy prices. However, this strategy would result in temporarily higher unemployment and factory closures in energy-intensive industries, would need to accommodate concerns over excessive reliance on imports and would need to be engineered to address carbon leakage. Policymakers should implement a mix of these policies. The EU should subsidise existing energy-intensive industries only in clearly justified cases, while deciding which energy-intensive products can be left to international market forces. By choosing which decarbonisation investments should be supported in Europe, the EU can combine industrial competitiveness and environmental sustainability.
Keywords: 330